The Histidine Decarboxylase Gene Cluster of Lactobacillus parabuchneri Was Gained by Horizontal Gene Transfer and Is Mobile within the Species - Wüthrich, Daniel; Berthoud, Hélène; Wechsler, Daniel; Eugster, Elisabeth; Irmler, Stefan; Bruggmann, Rémy (Frontiers in Microbiology, 2017)
Histamine in food can cause intolerance reactions in consumers. Lactobacillus parabuchneri (L. parabuchneri) is one of the major causes of elevated histamine levels in cheese. Despite its significant economic impact and negative influence on human health, no genomic study has been published so far. We sequenced and analyzed 18 L. parabuchneri strains of which 12 were histamine positive and 6 were histamine negative. We determined the complete genome of the histamine positive strain FAM21731 with PacBio as well as Illumina and the genomes of the remaining 17 strains using the Illumina technology. We developed the synteny aware ortholog finding algorithm SynOrf to compare the genomes and we show that the histidine decarboxylase (HDC) gene cluster is located in a genomic island. It is very likely that the HDC gene cluster was transferred from other lactobacilli, as it is highly conserved within several lactobacilli species. Furthermore, we have evidence that the HDC gene cluster was transferred within the L. parabuchneri species.